Mechanical Characterization for Cellular Mechanobiology: Current Trends and Future Prospects - Narasimhan, Badri Narayanan; Ting, Matthew S.; Kollmetz, Tarek; Horrocks, Matthew S.; Chalard, Anaïs E.; Malmström, Jenny (Frontiers in Bioengineering and Biotechnology, 2020)
Accurate mechanical characterization of substrates is important for understanding the influence of mechanical properties on the adhering cells. Recent mechanobiology studies outline the influence of mechanical parameters, such as stress relaxation, and strain stiffening on the behavior of cells. Numerous techniques exist for probing the mechanical properties of substrates for cell culture and it is vital to understand the benefits of each technique and how they relate to each other. This mini review aims to guide the reader through the toolbox of mechanical characterization techniques by presenting well-established and emerging methods currently used to assess mechanical properties of substrates and cells.